1990
DOI: 10.3382/ps.0691876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formic Acid or Calcium Formate in Feed on Performance and Microbiological Characteristics of Broilers

Abstract: Three experiments were conducted to determine the effects of feeding broilers formic acid (FA) or calcium formate (CF) on performance and microbiological characteristics of broilers. Live bird performance was not adversely affected by feeding up to 1.0% FA or 1.45% CF. In Experiment 1, levels of salmonellae in carcass and cecal samples were significantly reduced by feeding birds .36% CF. Salmonellae were not isolated from any of the carcasses of birds fed .36% CF. Similar reductions were not noted for total or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
2
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
5
21
2
9
Order By: Relevance
“…This is probably because of the strong buffering action of the poultry gastrointestinal tract. This result supports the previous findings reported by Izat et al 1990 andHernandez et al 2006, indicative of an antimicrobial action of the OAB in the upper alimentary tract. Therefore, the antimicrobial action of OAB in the gizzard might have reduced the number of the Enterobacteriaceae and increased the numbers of Lactobacillus in the small intestine as a compensatory mechanism.…”
Section: Intestinal Microbial Populationsupporting
confidence: 83%
See 1 more Smart Citation
“…This is probably because of the strong buffering action of the poultry gastrointestinal tract. This result supports the previous findings reported by Izat et al 1990 andHernandez et al 2006, indicative of an antimicrobial action of the OAB in the upper alimentary tract. Therefore, the antimicrobial action of OAB in the gizzard might have reduced the number of the Enterobacteriaceae and increased the numbers of Lactobacillus in the small intestine as a compensatory mechanism.…”
Section: Intestinal Microbial Populationsupporting
confidence: 83%
“…There were no significant interactions of DFA and OAB for growth performance. Similarly, previous researchers (Izat et al 1990;Waldroup et al 1995) also reported no effect on BW of broiler chicken with the use of formate and propionic acid in the broiler diet. However, Vogt et al (1982) and Skinner et al (1991) …”
Section: Growth Performancementioning
confidence: 94%
“…Similarly to this study, an 80% formic acid and 20% propionic acid mixture added at 1% to broiler chicken ration (Kaniawati et al, 1992), and 1% formic acid or 1.45% calcium formate (Izat et al, 1990a) did not affect live weight and feed-to-ratio at 42 days. However, Patten & Waldroup (1988) verified that the addition of 1.5% calcium formate to the ration reduced the weight of broiler chickens at 42 days.…”
Section: Resultsmentioning
confidence: 99%
“…Os ácidos propiônico e butírico reduziram, enquanto os ácidos fórmico ou acético aumentaram a colonização por Salmonella enteritidis (Van Immerseel et al, 2004). A adição de níveis crescentes de ácido propiônico resultou em diminuição da colonização de Escherichia coli no intestino delgado (Izat et al, 1990b). Os ácidos acético, propiônico e butírico têm ação trófica sobre a estrutura e o desenvolvimento intestinais, aumentando o tamanho dos vilos e a superfície de absorção (Sakata, 1987;Leeson et al, 2005).…”
Section: Introductionunclassified